2016
DOI: 10.7567/jjap.55.105601
|View full text |Cite
|
Sign up to set email alerts
|

Reexaminations of the effects of magnetic field on the nucleation of undercooled Cu melt

Abstract: The effect of a high static magnetic field on the nucleation of an undercooled Cu melt has been investigated using a glass slag fluxing technique in a 12 T superconductor magnet. Controlled heating cycles with and without a magnetic field are performed and the results indicate that the magnetic field has no single effect on the mean undercooling of undercooled Cu liquid, which is different from previous reports. The high static magnetic field can enhance the undercooling of Cu at first, and the effect is weake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In recent decades, steady magnetic fields (SMFs) have been widely applied in metallic materials processing, e.g., electromagnetic continuous casting, semiconductor crystal growth, crystal orientation, magnetic separation, and solidification processing, owing to their contactless interactions and different magnetic effects. , It has been found that an SMF can exert an influence on nucleation, the solid/liquid interface morphology, , melt undercooling, , etc. These phenomena imply that the SMF apparently modifies the interfacial properties.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, steady magnetic fields (SMFs) have been widely applied in metallic materials processing, e.g., electromagnetic continuous casting, semiconductor crystal growth, crystal orientation, magnetic separation, and solidification processing, owing to their contactless interactions and different magnetic effects. , It has been found that an SMF can exert an influence on nucleation, the solid/liquid interface morphology, , melt undercooling, , etc. These phenomena imply that the SMF apparently modifies the interfacial properties.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to an increase in the transferring time of the atom to nucleus, which, in turn, enhances the undercooling. Wang et al systematically investigated the effect of the SMF on the degree of undercooling [32,33]. It was found that the undercooling for homogeneous nucleation is irrelevant to the SMF intensity, but influenced undercooling for heterogeneous nucleation, as shown in Figure 4.…”
Section: Smf-induced Undercoolingmentioning
confidence: 99%
“…In recent decades, the steady magnetic field (SMF) has been widely applied to materials processing and it is frequently used to modify the microstructures and properties. For solidification processing, the SMF has been found to change the degree of undercooling of metal melts such as pure Cu [7,8], pure Al [9], pure Sn and pure Zn [10], and of alloy melts such as Ni-Cu [11] and Al-Cu [12,13]. Further, the researchers proposed various possible explanations to clarify the nature of the change in undercooling in an SMF, such as the delayed formation of the nucleationcatalyzed oxides [11] and the increase in solid/liquid interfacial tension due to the magnetic dipolar interaction [13].…”
mentioning
confidence: 99%